The regions of parametric instability of brush-contact device electromagnetic circuit in unstable working conditions (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The method to determine parametric instability regions of the electromagnetic circuit of the secluded brush contact of brush-contact device with using the oscillation equation  Mathieu II order for a dissipative system with one degree of freedom is developed. Recommendations on the selection of the parameters of the external damping device to eliminate the instability of electromagnetic waves in unstable working conditions brush-contact device are  given.